Az euró hazai bevezetésének újragondolása - Judit Neményi; Gábor Oblath (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
– The study aims to revisit some of the macroeconomic issues related to Hungary's eurozone-accession. The government postponed euro-adoption until 2020 without any explanation, which is one of the motivations of our analysis. We review the arguments formulated in 2000-2004 regarding the adoption of the euro by the profession, as well as the declarations and actual policies pursued by successive governments during the 2000-s. The study discusses the crisis within the euro area, the experiences of three central-east-European EU-countries having adopted the euro, and the modifications in EU economic governance, focusing at the implications for Hungary's euro-adoption. The main conclusion of the analysis is that, irrespective of when Hungary actually intends to join the eurozone, it is in the country's best interest to fulfil the requirements necessary for introducing the euro as early as possible. However, beyond the Maastricht-criteria, "internal" requirements have also to be met, involving the stabilisation of inflation expectations at a low level and, furthermore, that institutions and mechanisms be established, ensuring a close link between the evolution of productivity and wages. By declaring the will to meet these conditions, supported by actual policy measures, the credibility of economic policy could be enhanced and the conditions of economic convergence could be improved.
Keywords: F33; F35; E58; E65; 330; euro-adoption; crisis in the eurozone; country experiences in the eurozone; economic governance in the EU; Währungsumstellung; Euro; Eurozone; Wirkungsanalyse; Ungarn